Pengaruh Media Pembelajaran Interaktif Menggunakan Aplikasi Canva Terhadap Hasil Belajar Siswa Kelas VII Mata Pelajaran Pendidikan Agama Islam di SMPN 1 Ngraho Bojonegoro - Zumrotul Fauziyah; Ahmad Shofiyuddin; Intan Sukmawati (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
Abstract Rapid developments in technology and information have affected technology and information very rapidly. various aspects of life, so as to create new innovations in all fields, one of which is the field of education. In an effort to improve the quality of education, one of the things teachers can do is to use interactive learning media. With these technological advances, many applications are available easily and for free, one of which is Canva. Therefore, the researcher wanted to do an experiment using the Canva application. This can be used by teachers to facilitate the achievement of learning objectives and improve student learning outcomes. This study uses a quantitative approach with a sample of 32 students in the experimental class and 32 students in the control class. Data was collected using interview, documentation and test techniques (pretest and posttest). Data analysis techniques include normality test, homogeneity test, and hypothesis testing. Based on the research conducted, the following results were obtained: (1) The use of Canva interactive learning media in learning makes students more focused on the material presented, increases students' enthusiasm and motivation during the learning process, and makes the learning process in the classroom more lively and not boring, and (2) there is a significant influence between interactive learning media using the Canva application on the learning outcomes of class VII students of Islamic Religious Education subjects with a significance value of 0.000.